Comparison of The Efficacy of Audiovisual Tools and Intranasal Midazolam in Reducing Preoperative Anxiety in Pediatric Patients - Farrukh, Kalsoom; Ramzan, Muhammad Munib; Ikram, Adeela (Biological and Clinical Sciences Research Journal, 2025)
Preoperative anxiety is a common psychological challenge in pediatric surgical patients that can affect induction, recovery, and overall surgical experience. Both pharmacological and non-pharmacological interventions have been used to manage anxiety, with intranasal midazolam (INM) and audiovisual tools being among the most promising. This study aimed to compare the efficacy of audiovisual tools versus intranasal midazolam in reducing preoperative anxiety in children undergoing elective surgery under general anesthesia. Methods: This randomized controlled trial was conducted at the National Hospital and Medical Centre, Lahore, from May to November 2024. Sixty pediatric patients aged 5–13 years, ASA class I or II, were randomly assigned to two equal groups. Group A received audiovisual distraction (cartoons, movies, or video games), while Group B received intranasal midazolam (0.2 mg/kg, maximum 10 mg). Anxiety levels were measured using the Modified Yale Preoperative Anxiety Scale (mYPAS) at three time points: upon arrival (T1), 60 minutes before intervention (T2), and 15 minutes before induction (T3). Efficacy was defined as achieving an mYPAS score ≤30 before induction. Data were analyzed using SPSS v26.0, with p < 0.05 considered significant. Results: Both interventions effectively reduced preoperative anxiety, but the reduction was significantly greater in the audiovisual group. Mean mYPAS scores decreased from 45.93 ± 2.66 at T1 to 26.37 ± 3.66 at T3 in Group A, and from 44.83 ± 3.70 to 29.13 ± 4.83 in Group B. Effective anxiolysis (mYPAS ≤30) was achieved in 90% of patients in Group A versus 63.3% in Group B (p = 0.015). Audiovisual tools were particularly effective among younger (5–9 years) and female participants. No significant adverse events were reported in either group. Conclusion: Audiovisual tools demonstrated superior efficacy compared with intranasal midazolam in alleviating preoperative anxiety among pediatric patients. As a safe, non-invasive, and engaging alternative, audiovisual distraction should be considered a preferred approach for preoperative anxiety management, especially in resource-limited and pediatric-centered surgical settings.